2021
DOI: 10.3389/fcvm.2021.733339
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Analysis of Myocardial Work by Non-invasive Left Ventricular Pressure-Strain Loop in Patients With Type 2 Diabetes Mellitus

Abstract: Background: Type 2 diabetes mellitus (T2DM) is a common risk factor for cardiovascular diseases. The aims of this study were to evaluate the changes in the left ventricular myocardial work in T2DM patients using the left ventricular pressure-strain loop (PSL) technique, and to explore the risk factors for the left ventricular myocardial work impairment.Methods: Fifty patients with T2DM and 50 normal controls (NCs) were included in the study. In addition to conventional echocardiography and two-dimensional spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…This technique involves a combined analysis of LV GLS and brachial artery blood pressure, which overcomes the load dependence of LVEF and GLS and can more accurately assess myocardial work capacity. Previous studies have demonstrated that noninvasive myocardial work can help with the early assessment of myocardial damage among patients with hypertension, cardiomyopathy, and coronary artery disease, 18 patients undergoing synchronized therapy (CRT), 19 and those with myocardial amyloidosis, 20 systemic lupus erythematosus, 21 type 2 diabetes mellitus, 22 renal insufficiency 23 and other diseases. In this study, although the LVEF of the AF and control groups did not differ significantly, the MW parameters differed.…”
Section: Discussionmentioning
confidence: 99%
“…This technique involves a combined analysis of LV GLS and brachial artery blood pressure, which overcomes the load dependence of LVEF and GLS and can more accurately assess myocardial work capacity. Previous studies have demonstrated that noninvasive myocardial work can help with the early assessment of myocardial damage among patients with hypertension, cardiomyopathy, and coronary artery disease, 18 patients undergoing synchronized therapy (CRT), 19 and those with myocardial amyloidosis, 20 systemic lupus erythematosus, 21 type 2 diabetes mellitus, 22 renal insufficiency 23 and other diseases. In this study, although the LVEF of the AF and control groups did not differ significantly, the MW parameters differed.…”
Section: Discussionmentioning
confidence: 99%
“…42 Resting GWE value is closely related to LV systolic reserve and exercise capacity, and GWE during exercise is an independent predictor of significant LV systolic reserve. 60 Therefore, PSL may also have an evaluation and prediction role in some diseases that can cause LV dysfunction, [61][62][63][64][65] especially in chronic kidney disease. 66,67 Newly developed quantitative PSL technology provides a new method for clinical research to assess myocardial function.…”
Section: Discussionmentioning
confidence: 99%
“…These changes consequently lead to the deterioration of myocardial energy exploitation and metabolic activity, which may explain the reduction of GWI and GCW. Huang et al found that GWI and GCW were lower in patients with diabetes mellitus after adjusting for blood pressure and clinical parameters [ 36 ]. Moreover, GWI and GCW were reportedly higher in patients with Turner syndrome than in healthy individuals even though blood pressure and GLS were not significantly different [ 37 ].…”
Section: Discussionmentioning
confidence: 99%